2002
DOI: 10.1002/ijc.10441
|View full text |Cite
|
Sign up to set email alerts
|

Cancer risks in twins: Results from the Swedish family‐cancer database

Abstract: Twin studies on cancer have addressed two general questions, one about the possible carcinogenic effects of twinning and the second about heritable effects of cancer. The first question is answered by comparing the occurrence of cancer in twins to that in singletons; the second is answered in probandwise analysis of monozygotic twins compared to dizygotic twins or siblings. We used the nationwide Swedish Family-Cancer Database on 10.2 million individuals and 62,574 0 -66-year-old twins to calculate standardize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
22
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 36 publications
7
22
0
Order By: Relevance
“…We found, as have several others (4,6,7), that there is no reduction in overall risk of adult cancer among twins, although not all studies are in agreement, with some finding a small deficit in adult cancer incidence (5,30). Given the heterogeneity of adult cancers, however, such a grouping is unlikely to detect real differences in risk, particularly for rare cancers.…”
Section: Discussionsupporting
confidence: 70%
“…We found, as have several others (4,6,7), that there is no reduction in overall risk of adult cancer among twins, although not all studies are in agreement, with some finding a small deficit in adult cancer incidence (5,30). Given the heterogeneity of adult cancers, however, such a grouping is unlikely to detect real differences in risk, particularly for rare cancers.…”
Section: Discussionsupporting
confidence: 70%
“…In this study, they estimated the breast cancer incidence to be constant and approximately 1.3% per year, independent of age and duration of follow-up. More recently, Hemminki and Li (2002) have found this incidence rate to decrease with time since the diagnosis of the first twin, but the numbers in this study were small and therefore not necessarily inconsistent. Peto and Mack also note that this incidence rate is about twice the incidence rate for contralateral breast cancer (which are also roughly constant with time), consistent with the hypothesis that the high rate of contralateral breast cancer chiefly reflects genetic susceptibility (but with only one breast being at risk).…”
Section: Twin Studiesmentioning
confidence: 53%
“…In two previous studies, we observed a lower incidence of melanoma in twins as compared to singletons (Iversen et al, 2001;Franco-Lie et al, 2005) as have others (Hemminki and Li, 2002;Hemminki and Chen, 2005;Neale et al, 2005), but for which no biological explanation is evident.…”
supporting
confidence: 39%